Molecular bond stabilization in the strong-field dissociation of O2+ - Abanador, P. M.; Pauly, T.; Thumm, U. (My University, 2020)
We theoretically examine the rotational and vibrational dynamics of O2+ molecular ions exposed to intense, short laser pulses for conditions realized in contemporary pump-probe experiments. We solve the time-dependent Schrödinger equation within the Born-Oppenheimer approximation for an initial distribution of randomly aligned molecular ions. For fixed peak intensities, our numerical results show that total, angle-integrated O2+→O(3P)+O+(4S0) dissociation yields do not monotonically increase with increasing infrared-probe pulse duration. We find this pulse-duration-dependent stabilization to be consistent with the transient trapping of nuclear probability density in a light-induced (bond-hardening) potential-energy surface and robust against rotational excitation. We analyze this stabilization effect and its underlying bond-hardening mechanism (i) in the time domain, by following the evolution of partial nuclear probability densities associated with the dipole-coupled O2+(a4Πu) and O2+(f4Πg) cationic states, and (ii) in the frequency domain, by examining rovibrational quantum-beat spectra for the evolution of the partial nuclear probability densities associated with these states. Our analysis reveals the characteristic timescale for the bond-hardening mechanism in O2+ and explains the onset of bond stabilization for sufficiently long pulse durations.